2018
DOI: 10.1093/annonc/mdy460
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of carboplatin added to an anthracycline/taxane-based neoadjuvant chemotherapy and HRD score as predictor of response—final results from GeparSixto

Abstract: The addition of carboplatin to neoadjuvant PM improved DFS significantly in TNBC. Long-term survival analyses support the neoadjuvant use of carboplatin in TNBC. HR deficiency in TNBC and HRD score in non-tmBRCA TNBC are predictors of response. HRD does not predict for carboplatin benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
183
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(201 citation statements)
references
References 22 publications
6
183
0
12
Order By: Relevance
“…27 The use of PARP inhibition is also being explored in patients with early-stage breast cancer and germline BRCA mutations, including in the neoadjuvant and adjuvant settings. [28][29][30][31] The randomized OlympiA phase III study will examine adjuvant use of olaparib in patients with high-risk HER2-negative breast cancer with gBRCA mutations and should reveal whether PARP inhibition can improve outcomes in breast cancer if given in an earlier setting. 31 NOTE.…”
Section: Dna Damagementioning
confidence: 99%
“…27 The use of PARP inhibition is also being explored in patients with early-stage breast cancer and germline BRCA mutations, including in the neoadjuvant and adjuvant settings. [28][29][30][31] The randomized OlympiA phase III study will examine adjuvant use of olaparib in patients with high-risk HER2-negative breast cancer with gBRCA mutations and should reveal whether PARP inhibition can improve outcomes in breast cancer if given in an earlier setting. 31 NOTE.…”
Section: Dna Damagementioning
confidence: 99%
“…The results of this study strongly suggested that TNBC patients with HRD positive status treated with platinum-based NACT achieved more favorable response rates both in terms of pCR and residual cancer burden (RCB) compared to negative ones [28][29][30]. Similarly, in a retrospective analysis of Geparsixto, HRD TNBC patients randomized in the carboplatin arm achieved doubled pCR rates versus the non-HRD subgroup (63% and 29%, respectively), albeit without significant advantage in DFS or overall survival (OS) [31]. All these studies proved a strong correlation between HRD status and responsiveness to platinum-based NACT among TNBC patients.…”
Section: Brca1/2 Mutationsmentioning
confidence: 99%
“…В нескольких клинических испытаниях изучалось, улучшает ли исходная химиотерапия на основе платины результаты при ТНРМЖ [9] (Gepasixto, 2018; исследование BRIGHTNESS). Исследования НСТ последовательно показывают, что добавление химиотерапии на основе платины увеличивает частоту полного патоморфологического ответа при ТНРМЖ, хотя влияние на долговременное рецидивирование заболевания остается менее определенным, особенно если в лечение уже включен другой алкилирующий агент (т. е. циклофосфамид) [10]. Панель экспертов проголосовала против рутинного включения платины у пациенток с уже назначенными режимами химиотерапии алкилирующими препаратами, таксанами и на основе антрациклинов.…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified